Material selection for the mesh electrode of electrochromic device based on Ni(OH)2 - Kotok, Valerii; Kovalenko, Vadym (Eastern-European Journal of Enterprise Technologies, 2019)
In this study, we propose changes to the cell design in order to reduce the cost of electrochromic devices. The modification lies in the replacement of the second electrochromic layer along with its conductive layer with the mesh metal-oxide electrode. This variant of the electrochromic device is proposed to be installed in light windows and upper parts of view windows. For the proposed mesh electrode, a few possible electrochemical systems were proposed: Cu|Cu2O, Zn|ZnO, Ni|NiO and Ag|AgO. By means of cyclic voltammetry, the working parameters of these systems were found – working potential windows and specific peak current. Based on the obtained data, the silver electrode proved to be the most promising. The chosen electrode was studied by means of cyclic voltammetry and galvanostatic cycling. It was found that the specific capacity of the silver electrode does not have a strong dependence on the current density of oxidation and reduction. Minimum and maximum specific capacities of the studied electrode were found, which in 0.1 M КОН were 0.075 mA·h/cm2 (cyclic voltammetry) and 0.082–0.042 mA·h/cm2 (galvanostatic cycling). It was also found that during electrochemical cycling in 0.1 M KОН, the following transformations occur Ag↔Ag2O and Ag2O↔AgO. Based on the obtained data, at the specific capacity of the main (electrochromic) electrode of 0.011 mA·h/cm2, it is proposed to use a mesh with a 2x2 cell and wire diameter of 0.5 mm. It was found that the cost of the silver mesh can be decreased by using a silver plated copper mesh instead.